ChemInform Abstract: Synthesis of Functionalized Tryptamines by Broensted Acid Catalyzed Cascade Reactions. Issue 7 (January 2016) - Melis, Nicola; Secci, Francesco; Boddaert, Thomas; Aitken, David J.; Frongia, Angelo
Abstract: Solvent‐free PTSA‐catalyzed reaction between 2‐hydroxycyclobutanone and N‐alkylanilines gives tryptamine derivatives in low to good yields.